Community-level successes and challenges to implementing adolescent sex education programs. - Ott MA; Rouse M; Resseguie J; Smith H; Woodcox S (Maternal & Child Health Journal, 2011)
Best practices for adolescent sex education recommend science-based approaches. However, little is known about the capacity and needs of organizations who implement sex education programs on the local level. The purpose of this research was to describe successes and challenges of community organizations in implementing science-based sex education. Using qualitative methods, we interviewed program directors and educators in 17 state-funded adolescent pregnancy prevention/sex education programs as part of a larger mixed methods evaluation. Semi-structured interviews focused on success and challenges faced in implementing science-based approaches to program design, implementation and evaluation. Interviews were audio-recorded, transcribed and analyzed using a thematic approach. Grantees included a range of programs, from short programs on puberty and HIV for late elementary students, to skills-based curricular sex education programs for high schools, to year-long youth development programs. Key aspects of curricular choice included meeting the needs of the population, and working within time constraints of schools and other community partners. Populations presenting specific challenges included rural youth, youth in juvenile justice facilities, and working with Indiana's growing Latino population. Programs self-developing curricula described challenges related to assessment and evaluation of impact. Programs using commercial curricula described challenges related to curricular selection and adaptation, in particularly shortening curricula, and adapting to different cultural or social groups. A remarkable degree of innovation was observed. The use of qualitative methods permitted the identification of key challenges and successes in a state-sponsored small grants program. Information can be used to enhance program capacity and quality.